The Effects of Promotion and Site Attraction on Satisfaction and Subsequent Impact on Loyalty: A Case Study in Gunung Sewu Unesco Global Geopark, Indonesia - Sulistyadi, Budiono; Wening, Nur; Herawan, Tutut (Journal of Tourism Management Research, 2019)
Geopark as an innovation for the protection of natural and geological heritage plays an important role in the development of geotourism. All geoparks have to be established in rural areas, thus, geopark and geotourism are opportunities for rural development, reducing unemployment, and preventing migration in rural areas. This study aims to provide information for management to maintain and increase the number of geopark tourist visits. The research is conducted at the Gunung Sewu UNESCO Global Geopark in Gunungkidul district, Yogyakarta, Indonesia. The data collection is on January 2019 using a questionnaire of 50 respondents. The population is tourists visiting from 2013 to 2017; sample size is calculated based on Roscoe; type of probability sample, and sampling random sample. Research variable consists of the promotion and site attraction as independent variables, satisfaction as a mediator variable, and loyalty as the independent variable. This study examines the relationship between promotion and site attraction to satisfaction as a mediator variable and subsequent impact on loyalty. The analysis is carried out quantitatively by path analysis using linear structural relationship (LISREL) 8.50. The result shows that promotion does not have a direct affect on loyalty, still however affects on satisfaction. Thus, increasing promotion, therefore, it would provide opportunities for management to affects loyalty, which in turn could increase the number of tourist.